Caregiver experience with decision-making difficulties in end-of-life care for patients with cardiovascular diseases. Issue 4 (April 2022) - Shinada, Keitaro; Kohno, Takashi; Fukuda, Keiichi; Higashitani, Michiaki; Kawamatsu, Naoto; Kitai, Takeshi; Shibata, Tatsuhiro; Takei, Makoto; Nochioka, Kotaro; Nakazawa, Gaku; Shiomi, Hiroki; Miyashita, Mitsunori; et al.
Highlights: About 30% of caregivers experienced difficulties in decision-making during end-of-life (EOL) care. The most difficult situations involved communication about prognosis and life-prolonging treatment. Less EOL discussion, younger age of bereaved patients, and poor mental health were associated with decisional burden. The caregivers' decisional burdens were associated with subsequent psychological distress. Sufficient communication might be beneficial to prevent decisional burden. Abstract: Background: The decisional burden on caregivers in the end-of-life (EOL) care for patients with cardiovascular diseases (CVD) is unknown. We aimed to evaluate the frequency and circumstances of caregiver difficulties in decision-making during EOL care for CVD patients, its determinants, and associations with psychological distress in the bereaved caregivers. Methods: We conducted a cross-sectional survey using a questionnaire for bereaved caregivers of CVD patients who had died in 10 tertiary care centers. We assessed their overall and situation-specific decision-making difficulties during EOL care. The questionnaire also covered the attitudes of patients, caregivers, and attending physicians during EOL care and the respondents' depression (Patient Health Questionnaire-9) and grief status (Brief Grief Questionnaire). Results: We enrolled 266 bereaved caregivers [median age, 65 (57-72) years; 38.4% male] of CVD patients. Overall, 28.9% of them experienced difficulties in decision-making. The most difficult decision-making situations involved informing the patient of the prognosis (18.2%), life-prolonging treatment (17.9%), and discontinuation of hydration and artificial nutrition (15.6%). Difficulties were associated with patient and/or caregiver factors (poor understanding of disease status and the patient's wishes, caregiver's emotional inability), physician factors (poor understanding of the patient's and/or caregiver's values, inadequate support for decision-making), and both (insufficient communication, conflict of opinions and wishes). Decision-making difficulties were associated with subsequent depression (20.5% vs. 10.3%, p =0.029) and complicated grief (27.0% vs. 9.0%, p <0.001) among bereaved caregivers. Conclusions: Approximately 30% of bereaved caregivers experienced decisional burdens during EOL care of CVD patients. The caregiver's decisional burdens were associated with subsequent psychological distress.